Site-Directed Mutagenesis of Glu-269 L-Arabinose Isomerase from Geobacillus stearothermophilus Isolated from Tanjung Api Poso, Indonesia - Fitriani, Dewi Fitriani; Wulandari, Puspita Suci; Saksono, Budi (ANNALES BOGORIENSES, 2010)
Industrializing of tagatose requires enzymes that meet to industrial need such as thermophile, slightly acidic and metal independent.  Previously,  we  cloned,  sequenced  and  expressed  L-arabinose  isomerase  from  Geobacillus stearothermophilus  isolated  from Tanjung  Api, Poso, Indonesia. Based on DNA alignment analysis, the gene had  high  homology  with  those  of  G.  stearothermophilus  T6  (Gene  Bank  Acc  No:  AAD45718)  which  has optimum  activity  at  high  temperature  and  alkaline  condition.  In  this  p aper,  we  described  site-directed mutagenesis approach to mutate Glu-269 (Q269) to Lys-269 (K269) to decrease the optimum pH of the strain. Sequencing  result  showed  that  mutagenesis  had  been  successful  to  mutate  amino  acid  at  position  269  from glutamine (Q) into lysine (K). Expression of mutant Q269 showed protein with molecular mass ~56 kDa. Keywords: site-directed mutagenesis, Q269K, L-arabinose isomerase, Geobacillus stearothermophilus